"A very different kettle of fish": whole vessels from the Main Burial Complex at Crystal River (8CI1). Issue 3 (1st September 2020) - Pluckhahn, Thomas J.
ABSTRACT: The "allure of the exotic" dominates both the substance and practice of the archaeology of the Hopewell phenomenon in eastern North America. Ceramics have often been considered less important to Hopewellian exchange, perhaps because they are typically considered local products. I review whole vessels recovered by C. B. Moore from the Crystal River site (8CI1) and curated at the National Museum of the American Indian. Although limited to macroscopic description of form, paste, and decoration, this analysis suggests that ceramic vessels were commonly imported, probably mostly from other ceremonial centers within the region. More than just byproducts of broader interactions, extra-local ceramic vessels were integral to the development of Crystal River by materializing regional alliances and the metaphorical understanding of community as container.